Determinación del helicobacter pylori por la técnica inmunocromatográfica como ayuda de diagnóstico presuntivo de gastritis en los estudiantes de tercer año de bachillerato del colegio nacional chambo, provincia de chimborazo, en el período enero a junio de 2015 - Flores Olmedo, Janeth Marisela (2015)
Helicobacter pylori is a bacterium that infects the human gastric epithelium. Many ulcers and some types of gastritis due to Helicobacter pylori infections. In many cases, infected people never develop any symptoms. This brings up the current time it is accepted that this infection plays an important role in the genesis of gastritis, duodenal ulcer, peptic gastric ulcer and gastric cancer. With this background, the investigation sought to determine the importance of immunoassay technique for the detection of Helicobacter pylori in students of third year of high school College "National Chambo" in the period January to June 2015. The methods used in the research were deductive and inductive, and the type of research was explanatory, quantitative and descriptive. Depending on the type of proposed investigation (Explanatory, quantitative and descriptive) the hypothesis that has been proven is causal relationships. It concludes with the first specific objective, demonstrated and determined that the immunochromatographic technique, is 100% safe and suitable for laboratory work. The causes of the appearance of the bacterium Helicobacter pylori, are basically the lack of personal hygiene when using health, not washing hands before eating, eating food that has not been thoroughly washed and properly cooked, not disposing water in a healthy and clean source. In response the third specific objective, an extensive analysis was performed and bad habits of personal hygiene and bad eating habits, to thereby established, conduct a briefing with the delivery of educational materials on site.